External cervical resorption – current approach to etiology, diagnostics, and classification - Eliasz, Wojciech; Gawriołek, Maria; Kubiak, Kinga; Pukacki, Piotr; Juszkat, Robert; Surdacka, Anna (Journal of Stomatology, 2019)
External cervical resorption lesions (ECR) are becoming more and more frequently reported in dental literature, which is related to the fact that patients retain their natural teeth for longer, and also to an increase in the popularity of three-dimensional diagnostic imaging modalities. ECR constitutes an entity whose treatment and diagnostics remain difficult, and the prognosis for teeth affected by the disease is still relatively poor. Even though research studies have been conducted in various research centers worldwide, and even though the histopathological pattern and molecular events that accompany the development of ECR have been studied to a significant extent, the clinical factors that contribute to initiation and progression of ECR lesions have not been determined yet. The aim of the paper is to present the current state of knowledge concerning ECR etiology and diagnostics, and to present the current 3D classification system of ECR lesions that is based on cone beam computed tomography findings, as well as the clinical classification involving the accessibility of the lesion. The data may facilitate the choice of the most appropriate treatment method in patients who present with all stages of ECR, from the early ones, in which conservative treatment has a relatively good prognosis, to the most advanced ones, in which extraction is the treatment modality of choice.